Beneficial Effects of Yoghurts and Probiotic Fermented Milks and Their Functional Food Potential - Hadjimbei, Elena; Botsaris, George; Chrysostomou, Stavri (My University, 2022)
Probiotic fermented milks and yoghurts are acidified and fermented by viable bacteria, usually L. bulgaricus and S. thermophilus, resulting in a thicker product with a longer shelf life. They are a nutrition-dense food, providing a good source of calcium, phosphorus, potassium, vitamin A, vitamin B2, and vitamin B12. Additionally, they deliver high biological value proteins and essential fatty acids. There is accumulating evidence suggesting that yoghurt and fermented milk consumption is related to a number of health advantages, including the prevention of osteoporosis, diabetes, and cardiovascular diseases, as well as the promotion of gut health and immune system modulation. This review aims at presenting and critically reviewing the beneficial effects from the consumption of probiotic fermented milks in human health, whilst revealing potential applications in the food industry.
Keywords: fermented milk; functional food; health benefits; probiotics; yoghurt